Phase II Study of Bortezomib as a Single Agent in Patients with Previously Untreated or Relapsed/Refractory Acute Myeloid Leukemia Ineligible for Intensive Therapy. (28th April 2013) - Sarlo, Chiara; Buccisano, Francesco; Maurillo, Luca; Cefalo, Mariagiovanna; Di Caprio, Luigi; Cicconi, Laura; Ditto, Concetta; Ottaviani, Licia; Di Veroli, Ambra; Del Principe, Maria Ilaria; Grasso, Maria Assunta; Nasso, Daniela; et al.
Abstract : We explored the safety and efficacy of bortezomib given as single agent in patients with untreated or relapsed/refractory acute myeloid leukemia (AML), unfit for conventional chemotherapy. Fourteen patients were treated with bortezomib 1.5 mg/m 2 administered twice weekly for two weeks, every 3 weeks. Median age was 70 years (range 60–81) and the median number of cycles delivered was 2 (range 1–4). Of 13 evaluable patients, in 8 (61%), the administration of bortezomib resulted in an antileukemic effect as demonstrated by peripheral blood and/or bone marrow blast reduction. In 4 (50%) of these 8, a decrease by 37% of transfusion requirement was also observed( P = 0.009 ) . Overall median survival was 4 months (range 0.25–10). Neurotoxicity was the most frequent adverse event with 7 of 13 (54%) patients experiencing grades 3-4 peripheral neuropathy. Neurotoxicity led to treatment discontinuation in 4 (57%) of 7. In conclusion, the observed anti-leukemic activity of bortezomib indicates that there is room for designing additional studies in which combination with other chemotherapeutic agents should be considered. Clinical registration no.: EUDRACT 2006-006923-38.